Cover crops to regenerate soils and increase profitability in dryland crop production in the semi-arid central Great Plains - Simon, Logan M. (Kansas State University, 2024)
Replacing fallow with dual-purpose cover crops (CCs) could enhance soil health and increase cropping system profitability when CCs are grazed or hayed by providing an economic benefit to offset potential lost revenue when crop yields are reduced after CCs in dry years. However, there is concern that removing CC biomass could limit the beneficial effects of CCs for soil health and that soil compaction may occur with grazing on no-till (NT) fields, which could limit subsequent crop yields and require tillage for remediation. Flexible CC management has also been introduced as a possible strategy to take advantage of plant available water (PAW) in wet years while saving PAW for primary crops in dry years. From 2015 to 2023, a series of small-plot and on-farm experiments were conducted to determine the best management strategies for CCs to replace fallow in NT dryland cropping systems of the semi-arid central Great Plains (CGP). Studies investigated 1) grazing and haying CCs as forage, 2) interactions of CCs and tillage [NT or occasional tillage (OT)], 3) CC mixture diversity, and 4) flexible fallow-replacement based on PAW and climate outlooks. In each case, strategies were evaluated for impacts on PAW, grain and forage production, system profitability, and soil properties. Results showed that spring-planted cool-season CCs grown in place of fallow before wheat (Triticum aestivum L.) produced about 3100 kg biomass ha⁻¹ on average. Grazing removed about 40% of the available forage while haying removed about 70%. Crop residue cover was greater with CCs (80%) compared to fallow (68%), but profile PAW at wheat planting was about 21 mm greater with fallow than with CCs. Average wheat yields were unaffected by fallow management or tillage, but fallow management effects varied across years. Net returns were in the order of grazed CCs as an alternative to confined hay feeding > hayed CCs > flex-hayed CCs > grazed CCs as an alternative to grazing rangeland > fallow > standing CCs. When planted, CCs increased crop residue cover, particulate organic carbon, and water stable aggregates compared to fallow. Crop residue cover with NT (86%) was greater than OT (67%), but profile PAW, grain yields, net returns, and most soil properties were unaffected by tillage though the wind-erodible fraction was greater with OT compared to NT. Warm-season CCs planted immediately after wheat harvest produced about 3800 kg biomass ha⁻¹ on average. Average grain sorghum (Sorghum bicolor Moench) yields were 11% less following standing or grazed CCs compared to fallow but yields following hayed CCs were similar to fallow. Net returns were in the order of grazed CCs (as an alternative to confined hay feeding) > hayed CCs > grazed CCs (as an alternative to grazing rangeland) fallow > standing CCs. Soil properties were unaffected by warm-season CC management compared to fallow. On-farm evaluations of CC grazing impacts in NT systems further demonstrated that CC biomass left as residue post-grazing was similar to pre-grazing and was 60% of the ungrazed CCs. Most soil properties were not different between grazed and ungrazed CCs. However, soil organic carbon and potassium concentrations were greater with grazed CCs compared to ungrazed CCs possibly due to substantial CC residue remaining following grazing coupled with manure deposition. These results suggest that dual-purpose CCs for grazing or haying can provide forage for livestock, increase crop residue cover and soil aggregate stability, maintain crop yields, and increase net returns in NT systems with limited risk of soil compaction. However, results are likely to differ based on stocking rate, category of livestock, duration of grazing, and available CC biomass for grazing or haying cutting height. Further research will be needed to determine the long-term effects of CC grazing in NT systems as well as to determine optimum rates of CC biomass removal with grazing to optimize farm income and enhance soil health in NT dryland cropping systems. Furthermore, our results suggest CC mixtures should be simple and dominated by productive grasses species to maximize forage and residue production. If OT is necessary in a long-term NT system to correct root-limiting compaction, PAW, crop yields, net returns, and soil properties are generally unaffected compared to NT. Flexible CC management systems might still be a useful strategy in the semi-arid CGP to avoid severe wheat yield reductions following CCs in extremely dry years. However, more site-year observations will be required to better understand the impact of flex-CCs, and increased accuracy of precipitation outlook models will also be required for flex-CCs to successfully be adopted in this region.
Keywords: Dryland; Cover crops; Forage; Compaction; Soil organic carbon; Aggregate stability